Population structure and reproductive period of the tropical hermit crab Calcinus tibicen (Decapoda : Diogenidae) in the region of Ubatuba, São Paulo, Brazil - Fransozo, A.; Mantelatto, FLM (Crustacean Soc, 1998)
The population of the hermit crab Calcinus tibicen in the Ubatuba region was studied with emphasis on seasonal abundance, seasonal size-frequency distribution, sex-ratio, and reproductive period based on the percentage of ovigerous females. The animals were collected at 2-month intervals for 2 consecutive years (from January 1993 to November 1994). Total mean animal size in shield length was 5.14 +/- 1.23 mm for males, 4.23 +/- 0.79 mm for females, and 4.53 +/- 0.60 for ovigerous females. A discontinuity in reproduction was observed, with an absence of ovigerous females in July (winter) and a high incidence from September to May (spring to autumn). Calcinus tibicen is sexually dimorphic in relation to size, with a higher growth rare in males. The sex-ratio pattern changes with season, indicating that it is more a function of season or habitat than of size.